Temporal increase in migratoriness and increasing male bias among residents in partially migrating Swedish sparrowhawks Accipiter nisus - Otterbeck, Andreas; Lindén, Andreas (Suomen lintutieteellinen yhdistys, 2024)
Partial migrants have populations consisting of both migratory and resident individuals. These migrants and residents experience unequal ecological conditions during winter and the underlying factors driving their decision to stay on their breeding grounds or to migrate remain debated—both from the viewpoint of populations and individuals. Here, we studied partial migration in a small raptor, the Eurasian Sparrowhawk (Accipiter nisus), from two different but interconnected perspectives: 1) explaining the patterns and variation in the ratio of migrants to residents (migratoriness) at the population level and 2) revealing how age and sex may affect the individual decision to be migratory or resident. We used citizen observation data over four decades to explore the temporal and spatial variation in the age and sex ratio of wintering resident sparrowhawks in Sweden. We found that the migratoriness unexpectedly increased with higher annual temperatures and showed long-term trend across the study period. Also, this migrant-to-resident ratio increased with smaller winter prey abundance. The average winter sex ratio was male-biased and became increasingly so over the years. We suggest that residency benefits territory-establishing males as early presence gives a competitive advantage in obtaining high-quality territories. Moreover, the distribution of overwintering individuals (regardless of sex) moved gradually northwards as the winter progressed, suggesting that smaller-scale migration occurs among the resident fraction of the population. These results provide suggestions for the underlying drivers and regulation of partial migration.
Keywords: migration; life history; climate change; partial migration; reversed size dimorphism